In Vitro Susceptibilities of Anaerobic Bacteria to Josamycin - Long, Sarah S. (1976)
A total of 132 strains of anaerobic bacteria were tested for susceptibility to josamycin, using a broth dilution technique. All strains of Peptococcus species, Peptostreptococcus species, and Bacteroides fragilis were inhibited by 2 μg or less per ml. Seventy percent of these susceptible strains were also killed by 2 μg or less of josamycin per ml. However, 2 of 12 Clostridium species and 6 of 10 Fusobacterium species had minimum inhibitory concentrations of 32 μg or more per ml.